2017
DOI: 10.1177/1756829316669957
|View full text |Cite
|
Sign up to set email alerts
|

A CFD-based procedure for airspace integration of small unmanned aircraft within congested areas

Abstract: Future integration of small unmanned aircraft within an urban airspace requires an a posteriori understanding of the building-induced aerodynamics which could negatively impact on vehicle performance. Moving away from generalised building formations, we model the centre of the city of Glasgow using Star-CCMþ, a commercial CFD package. After establishing a critical turbulent kinetic energy for our vehicle, we analyse the CFD results to determine how best to operate a small unmanned aircraft within this environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The areas with higher TKE are located around buildings that stand at the most upstream against the wind direction, and these areas increase in size and TKE levels with higher wind speed. The TKE calculated from the wind simulation in this study is lower than the critical TKE value of 6 J/kg assigned by Murray and Anderson in their study [13], and this is due to the lower wind reference speeds that were used in this study such that little to no areas within the building complex reach the critical TKE value.…”
Section: Velocity Field From Different Inlet Wind Speedscontrasting
confidence: 75%
See 1 more Smart Citation
“…The areas with higher TKE are located around buildings that stand at the most upstream against the wind direction, and these areas increase in size and TKE levels with higher wind speed. The TKE calculated from the wind simulation in this study is lower than the critical TKE value of 6 J/kg assigned by Murray and Anderson in their study [13], and this is due to the lower wind reference speeds that were used in this study such that little to no areas within the building complex reach the critical TKE value.…”
Section: Velocity Field From Different Inlet Wind Speedscontrasting
confidence: 75%
“…From the obtained time-averaged solution of CFD simulation [11], Watkins et al [12] focused on the change in flow velocity magnitude and angles due to the shear flow over a building's roof. Murray and Anderson [13] showed that the stability of UAS is dependent on the Turbulence Kinetic Energy of the wind field, and therefore UAS operations should be mindful of their operating conditions such as the altitude, wind speed and direction. To allow further adoption of UAS technology within urban environments, the safety of all inhabitants and infrastructures within them has to be guaranteed first to prevent any casualties due to UAS accidents.…”
Section: Introductionmentioning
confidence: 99%
“…In an urban environment, dense buildings and wind field make the trajectory planning for quadrotor challenging. 15 A real-time route planning method is proposed in Wei et al. 16 for obstacle avoidance among buildings in an unknown urban area.…”
Section: Introductionmentioning
confidence: 99%
“…In an urban environment, dense buildings and wind field make the trajectory planning for quadrotor challenging. 15 A real-time route planning method is proposed in Wei et al 16 for obstacle avoidance among buildings in an unknown urban area. Firstly, the Laguerre route is induced for a single prepared flight aisle between two buildings based on the basic principle of Laguerre diagram.…”
Section: Introductionmentioning
confidence: 99%